Prescription pattern in ischemic heart disease inpatients at B. P. Koirala Institute of Health Sciences: a cross sectional study - Rai, Dillisher; Rauniar, Gajendra Prasad; Shah, Prashant; Pandey, Dipesh R.; Mandal, Namita K.; Sarraf, Deependra P. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Drug utilization pattern studies seek to screen, evaluate and suggest appropriate modifications in prescription practices. It would help to make patient care rational and cost effective. Objective was to analyze the drug prescribing pattern for treatment of ischemic heart disease (IHD). Methods: A prospective cross-sectional observational study was conducted in patients of IHD admitted in intensive coronary care unit and medicine ward for the period of six months. Data were collected in preformed case record form. The data were analyzed for drug use indicators, demographic parameters, morbidities, pattern of drug use using Microsoft excel 2010. Results: A total of 145 patients were enrolled out of that 89 (61.38%) were males. The mean age was 60.01±12.71 years and majority (26.89%) belonged to age group of 61-70 years. A total of 1208 drugs were prescribed in 145 patients. Most frequently prescribed drugs were antiplatelet group of drugs 100% encounters, followed by hypo-lipidemics (98.62%). Average number of drugs per encounter was 8.33 and percentage of drugs prescribed by generic name was 5.04%. Conclusions: IHD was more common in males than females. The most commonly prescribed drug classes were anti-platelet drugs followed by hypolipidemic agents.